Cafetería café cultura - Cruz Bernal, Karen Paola (2014)
Café Cultura is responsible for offering a Premium service and a high quality to is customers by publicizing the culture of Quito and collecting the stories that identify us as a culture, taking an environment of relaxation and fun. Providing quality service and trained and caring diner staff. The music setting will be a classic genre because this type of music leads to tranquility and serenity which is what we wish to offer our customers. Performances and art spaces will be given, in order to promote the art of Quito. This space will be used solely for artistic expression and freedom of citizens. The furniture will have a variety of style as well as in color, thus giving the place elegance and exclusivity. Creating a fun space for Young customers, there will be a karaoke located in a special part, this will avoid disturbing other customers who would like a more serious and quiet environment. The best food in Quito will be dispatched in Café Cultura. We want to encourage both fast food cuisine and gourmet food. Working day and night to meet our given business objectives…